2008
DOI: 10.1037/0021-843x.117.1.225
|View full text |Cite
|
Sign up to set email alerts
|

Eating pathology among adolescent girls with attention-deficit/hyperactivity disorder.

Abstract: Investigated prospectively-assessed eating pathology (body image dissatisfaction and bulimia nervosa symptoms) among an ethnically and socioeconomically diverse sample of adolescent girls with ADHD-Combined Type (ADHD-C; n=93), ADHD-Inattentive Type (ADHD-I; n=47), and a comparison group (n=88). The sample, initially aged 6-12 years, participated in a 5-year longitudinal study (92% retention rate). After statistical control of relevant covariates, girls with ADHD-C at baseline showed more eating pathology at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(100 citation statements)
references
References 81 publications
11
84
3
1
Order By: Relevance
“…Of these, seven articles met full criteria for inclusion and one article was identified from the reference lists of the included articles. Thus, eight articles are summarized in the present review [17][18][19][20][21][22][23][24]. Figure 1 depicts the article selection and review process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, seven articles met full criteria for inclusion and one article was identified from the reference lists of the included articles. Thus, eight articles are summarized in the present review [17][18][19][20][21][22][23][24]. Figure 1 depicts the article selection and review process.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [22,24] were performed on large populationbased datasets and a third study was based on a large community sample of adolescents [21]. Four studies were comprised of large samples of youth with ADHD ascertained within clinical settings or specialized camps designed for research in children with ADHD [17][18][19][20]. One study was comprised of inpatients hospitalized for eating isorders [23].…”
Section: Resultsmentioning
confidence: 99%
“…Results from several investigations suggest that if children with ADHD are rejected by peers, this augments the risk associated with ADHD diagnostic status for depression, anxiety, delinquency, academic failure, eating pathology, and substance abuse in adolescence [24][25][26]. Recent evidence finds that, in addition to ADHD symptoms predicting peer problems, peer rejection may actually exacerbate ADHD symptoms over the course of a year [27•].…”
Section: Implications Of Peer Problems For Maladjustmentmentioning
confidence: 99%
“…Even so, it is clear that ADHD is associated with considerable functional and psychosocial impairment in girls, including an increased risk of internalizing disorders (eating disorders, depression, suicide), especially in adolescence and young adulthood Gershon, 2002;Makris et al, 2008;Mikami et al, 2008]. Longitudinal follow-up of a large cohort of girls with ADHD aged 6-18 years at baseline showed that girls with ADHD were at significantly higher risk for elevated prevalence of antisocial, addictive, mood, and anxiety disorders, including Major Depression, Bipolar Disorder, Tourette syndrome, and Nicotine Dependence [Biederman et al, 2006].…”
Section: Adhd In Girlsmentioning
confidence: 99%